THE IMPLEMENTATION OF ENGLISH CROSS INTEREST IN SENIOR HIGH SCHOOL - Cucum Rohmawati; Yazid Rukmayadi; Dede Rohadi Fajri (FKIP, Universitas Banten Jaya, 2023)
Cross interest in 2013 curriculum is a new program and government’s policy. Its purpose is giving opportunities for students to select and study the cross-interest subjects. Due to the important of English and needed by the students, it’s supposed that an analysis of English Cross Interest is crucial to be implemented to know the effectiveness of English Cross Interest in helping the students to meet their real needs and improve their English mastery. In doing this research, literature study, observation and interview with the teachers of English Cross Interest and students of senior high school in Kota Serang were carried out to obtain the data needed. Based on research and analysis conducted, it can be concluded that education was really needed in human life. But through the changing of curriculum, it arose several new things which were problems for several teachers. This case was happened in changing the previous curriculum to the new one, that was Education Unit Level Curriculum to be 2013 Curriculum.